1998
DOI: 10.1159/000027374
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic Therapy with Low-Dose Recombinant Tissue Plasminogen Activator in Retinal Vein Occlusion

Abstract: Fibrinolytic therapy aimed at early restoration of blood flow appears to be a promising therapeutic approach in haemorrhagic retinopathy. The risk of bleeding complications, a major problem with fibrinolysis, can be reduced by the use of low-dose thrombolytic regimens. In our study, 14 patients with ischaemic central (CRVO) or branch (BRVO) retinal vein occlusion who presented with severe visual loss and recent onset of symptoms were treated with a low dose (50 mg) of recombinant tissue plasminogen activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 21 publications
1
19
0
2
Order By: Relevance
“…In another study, a more favorable outcome after treatment of CRVO and branch retinal vein occlusion with streptokinase in comparison to anticoagulant therapy with heparin was observed [25]. Moreover, several investigators have reported on a beneficial effect of rtPA in the management of CRVO and branch retinal vein occlusion, but the numbers of patients enrolled in these studies were small [21, 22, 24, 30], and most investigators administered higher doses of rtPA (70 mg) in a nonfrontloaded manner, followed by continuous intravenous heparinization over a maximum period of 72 h. A large body of evidence for the effectiveness of rtPA in retinal vein occlusion, however, has been provided by several experimental studies [31, 32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, a more favorable outcome after treatment of CRVO and branch retinal vein occlusion with streptokinase in comparison to anticoagulant therapy with heparin was observed [25]. Moreover, several investigators have reported on a beneficial effect of rtPA in the management of CRVO and branch retinal vein occlusion, but the numbers of patients enrolled in these studies were small [21, 22, 24, 30], and most investigators administered higher doses of rtPA (70 mg) in a nonfrontloaded manner, followed by continuous intravenous heparinization over a maximum period of 72 h. A large body of evidence for the effectiveness of rtPA in retinal vein occlusion, however, has been provided by several experimental studies [31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the spectrum of indications for thrombolytic drugs such as streptokinase or recombinant tissue plasminogen activator (rtPA) comprises lung embolism, ischemic stroke, deep-vein thrombosis and acute arterial occlusions of the lower limbs [17, 18, 19, 20]. In contrast, the use of thrombolytic agents in retinal vessel occlusion is in its infancy, although several studies have indicated that fibrinolysis may be associated with a better visual prognosis in CRVO [21, 22, 23, 24, 25]. Since, basically, it is of some concern that the systemic administration of fibrinolytic agents carries a risk of bleeding, the choice of an appropriate intravenous thrombolytic therapy in a non-life-threatening situation should be based on minimizing the probability of potential complications.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the progression of the CRVO and the rapid deterioration in visual acuity, fibrinolytic treatment was started on day 8 [3]. We administered 50 mg of recombinant tissue plasminogen activator intravenously over a period of 60 min.…”
Section: Case Reportsmentioning
confidence: 99%
“…Recombinant tissue plasminogen activator (rtPA) is a synthetic fibrinolytic agent that converts plasminogen to plasmin and destabilizes intravascular thrombi. rtPA, as therapy against CRVO, has been administered by several routes: systemic [13,14], intravitreal [15,16,17], and by endovascular cannulation of retinal vessels either through a neuroradiological or a vitreoretinal approach, and delivery of minute quantities of rtPA directly to the occluded vessels to release the suspected thrombus [18,20,21]. …”
Section: Central Retinal Vein Occlusionmentioning
confidence: 99%